PENGEMBANGAN MEDIA ULAR TANGGA BERBASIS MODEL LOK-R BERMUATAN BUDAYA LOKAL BANTEN DI KELAS IV SD - Komariah, Iis; Jamaludin, Ujang; Taufik, M. (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2025)
This study aims to determine the feasibility, student responses, and to determine the increase in students' understanding of Banten local culture after using the Snakes and Ladders Media Based on the LOK-R Model Containing Banten Local Culture. The study used the Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques in the study were interviews, observations, questionnaires, tests, and documentation. The subjects of this study were grade IV students of SDN Sukamanah. The results of the study showed that the validation of material experts obtained a percentage of 93%, expert validation 89%, and language expert validation 93%, all three were included in the "Very Feasible" category with an overall percentage of product feasibility reaching 92% in the "Very Feasible" category. The results of the product trial on students obtained an average score of 93% in the "Very Good" category. Furthermore, the results of the pre-test post-test increased from 57 (Need Guidance) to 90 (Very Good). Thus, the Snakes and Ladders Media Based on the LOK-R Model Containing Banten Culture is very suitable for use and is able to improve the learning outcomes of grade IV elementary school students.